The effectiveness of kinesiotherapy in pelvic organ prolapse in women (Research, Society and Development, 2022)
Pelvic organ prolapse (POP) in women is the descent of pelvic organs towards the vaginal canal due to weakness or deficits in the ligaments, fascia and muscles of the pelvic floor. Because POP is a health problem that affects millions of women around the world, pelvic physiotherapy has been assuming an important role, due to its positive result in the treatment of POP and because it is a highly effective resource. Among the therapeutic resources used in POP, there are those that work with the strengthening of the pelvic floor muscles, they are: electrostimulation, Biofeedback, the use of vaginal cones and kinesiotherapy based on Kegel exercises. The main objective of this study is to analyze through the proof of the effectiveness of kinesiotherapy in the treatment of pelvic organ prolapse in women, as it has great relevance in society and in women's health as it is a dysfunction that affects about 40% of women. This study is a literature review, descriptive and exploratory, with a qualitative approach. Its basis for theoretical discussion is scientific articles and other intellectual productions. The inclusion criteria were: articles and intellectual productions published, covering the period from 2015 to 2021. The main physical therapy tool is the performance of exercises for the PFM, which aims to improve the strength of contraction of muscle fibers and resistance of the muscles of the perineal region.